2023
DOI: 10.1371/journal.pone.0282008
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation effect of mallotojaponin B on chloramphenicol and mode of action of combinations against Methicillin-resistant Staphylococcus aureus

Abstract: Staphylococcus aureus, the causative agent of many infectious diseases has developed resistance to many antibiotics, even chloramphenicol which was the essential antibiotic recommended for the treatment of bacterial infection. Thus, other alternatives to fight against S. aureus infections are necessary; and combinatory therapy of antibiotics with natural compounds is one of the approaches. This study evaluated the activity of the combination of mallotojaponin B and chloramphenicol against Methicillin-resistant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…From susceptibility assays, S. flexneri appeared as moderately resistant (MIC ≥ 8 µg/mL) towards cotrimoxazole and ceftriaxone (common MIC = 12.5 µg/mL) according to the classification criteria defined by Walsh [64]. Nguena-Dongue et al [65] emitted the same conclusion when evaluating the potentiation effect of mallotojaponin B on chloramphenicol against methicillin resistant Staphylococcus aureus. Several authors reported the resistance of S. flexneri to both cotrimoxazole and ceftriaxone [7,13].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…From susceptibility assays, S. flexneri appeared as moderately resistant (MIC ≥ 8 µg/mL) towards cotrimoxazole and ceftriaxone (common MIC = 12.5 µg/mL) according to the classification criteria defined by Walsh [64]. Nguena-Dongue et al [65] emitted the same conclusion when evaluating the potentiation effect of mallotojaponin B on chloramphenicol against methicillin resistant Staphylococcus aureus. Several authors reported the resistance of S. flexneri to both cotrimoxazole and ceftriaxone [7,13].…”
Section: Discussionmentioning
confidence: 91%
“…Combinatory assessment of compounds 4a and 4b with cotrimoxazole and ceftriaxone using a checkerboard method revealed a synergistic effect (mean FICI= 0.14) with significant MIC reduction (from 12.5 µg/mL to 0.097 µg/mL) suggesting a mutual potentiation of both compounds and antibiotics [41]. Nguena-Dongue et al [65] mentioned the same antibacterial effect when he obtained a reduction in the MIC value of mallotojaponin B from 12.5 to 0.781 µg/ mL when combined with chloramphenicol. The optimal ratio combinations (with the lowest FICI) exhibited MIC values ranging from 0.625 (4b-Cef) to 2.5 µg/mL (4a-Cot) against S. flexneri, confirming 4b derivative as the best candidate for combination with both the ceftriaxone and cotrimoxazole.…”
Section: Discussionmentioning
confidence: 97%
“…These results demonstrated that the combination of mallotojaponin B and chloramphenicol exerts bactericidal synergistic effects on MRSA through the alteration and destruction of the cell membrane and biofilms formed by MRSA, suggesting that this combination could be a potential strategy against methicillin-resistant S. aureus (Table 1; Figure 1). chloramphenicol was demonstrated [128]. These results demonstrated that the combination of mallotojaponin B and chloramphenicol exerts bactericidal synergistic effects on MRSA through the alteration and destruction of the cell membrane and biofilms formed by MRSA, suggesting that this combination could be a potential strategy against methicillin-resistant S. aureus (Table 1; Figure 1).…”
Section: Synergy Between Antibacterial Chemotherapeutics and Natural ...mentioning
confidence: 82%
“…Nguena-Dongue and colleagues investigated the effects of their combinations against MRSA. Interestingly, a synergistic effect (FICI 0.393) with MIC reductions in a range from 12.5 µg/mL (MIC) to 0.781 µg/mL (1/16 MIC) for mallotojaponin B and from 250 µg/mL (MIC) to 1.95 µg/mL (1/128 MIC) for chloramphenicol was demonstrated [128]. These results demonstrated that the combination of mallotojaponin B and chloramphenicol exerts bactericidal synergistic effects on MRSA through the alteration and destruction of the cell membrane and biofilms formed by MRSA, suggesting that this combination could be a potential strategy against methicillin-resistant S. aureus (Table 1; Figure 1).…”
Section: Synergy Between Antibacterial Chemotherapeutics and Natural ...mentioning
confidence: 99%
“…Therefore, MRSA biofilm infections are one of the main concerns in the global public health sector. Currently, there are no effective drugs targeting MRSA biofilms in clinical practice ( Jolivet-Gougeon and Bonnaure-Mallet, 2014 ; Nguena-Dongue et al, 2023 ). Therefore, the development of new drugs to treat MRSA infection is increasingly urgent.…”
Section: Introductionmentioning
confidence: 99%